EMOTIONAL RELIANCE AND LACK OF SELF-CONFIDENCE AS CORRELATES OF PROBLEMATIC MOBILE PHONE USE AMONG UNDERGRADUATES - Ngozi, Nnamani Anastesia; F, Asiegbu Martin; Chibuike, Okoli Paul; Philip, Ofojebe Chukwuma (International Journal of Psychosocial Rehabilitation, 2020)
This study investigated emotional reliance and lack of self-confidence as correlates of problematic mobile phone use among undergraduate. Data was collected from a total sample of 220 undergraduates (117 males and 103 females) students of Nnamdi Azikiwe University Awka and Federal Polytechnic Oko with age range between 17-30 years with a mean of 22.77, range of 13 and standard deviation of 2.97. Problematic mobile phone use questionnaire (PMPUQ), emotional reliance subscale and lack of self-confidence subscale of interpersonal dependency inventory (IDI) were used for data collection. It was a survey design and Pearson Moment Correlation Coefficient was employed for data analysis using Statistical Package for Social Sciences (SPSS 17.0) The findings of this study reveals that there is a positive relationship between emotional reliance and problematic mobile phone use among undergraduates and that lack of self-confidence have a positive significant relationship with problematic mobile. The implication is this study is that is need parents/ teachers as well as policy makers to the regulation of mobile phone use among undergraduates and it calls on psychologist to step up campaign and training on so social skill especially on self-confidence, emotional reliance, assertiveness and self-efficacy. This study recommend that the University, Government agencies, parents, and the general public should embark on awareness campaign to enlighten the public especially the young people on the dangers, or negative effects of mobile phone abuse